Recovery & Survival Strategies of The Impact of Covid-19 at Hotel Losari Villas-Legian and Hotel Losari Sunset Road Bali - Widawati, Ida Ayu Putri; Damayanti, Titien; Mareni, Ni Ketut; Tuwi, I Wayan (E-Journal of Tourism, 2023)
The Covid-19 Pandemic outbreak has caused the economic sector to decline drastically and especially Bali tourism on all fronts, because the tourism sector is the mainstay of the Balinese economy. This impact was also experienced by the hotel industry with a decrease in THK. This research aims to explore how the impact of Covid-19 has had on THK, ADR and Revpar Hotel Losari Villas-Legian and Hotel Losari Sunset Road Bali, and how strategies for survival and recovery strategies have been implemented to survive. This hotel has a different target market, Hotel Losari Villas Legian with the target market for foreign tourists, and Hotel Losari Second Sunset Road with the target market for wisdom. This exploratory qualitative research approach was carried out for the period August - October 2021 through observation, interviews, literature study. Qualitative and quantitative data are processed by means of Data Collection; Data Reduction; Display Data; Figure Conclusion and Verification, obtained from cost controller, sales and marketing manager, human resource manager, revenue manager, general manager and hotel owner. Contingency Plan theory includes Incident Response Disaster, Disaster Recovery Plan, Business Continuity Plan, and RTO, RPO, MTD, and WRT Route Maps to analyze how the stages of dealing with a hazard situation, and the ability to overcome a disaster or crisis that occurs. The results of this study indicate that THK, ADR, RevPar have decreased which resulted in decreased hotel revenue. Also, carry out a survival strategy to maintain the resilience of the hotel business by carrying out strategies in marketing, HR, operations, finance, IT and research and development; Recovery Strategy by developing a Strategic Recovery Plan Model with six stages of a strategic recovery plan. The implementation of the survival strategy and recovery strategy provides benefits for hotel management to continue to run hotel operations. Keywords: room occupancy rate, average daily rate, revpar, hotel revenue, hotel business resilience